Estimation of Carbon Stocks in Five Years Old Mangrove Stands in Jakarta - Kusmana, Cecep; Amanta, Neysa Nurma (Journal of Tropical Silviculture, 2024)
Global warming is an increase in the average temperature of the earth's surface due to the effects of greenhouse gases, such as carbon dioxide. Global warming can be prevented by maintaining forest structure and increasing tree density in the forest, one of which is in the mangrove forest ecosystem through rehabilitation using bund techniques. This research aims to analyze the type composition and structure of mangrove stands, estimate carbon storage and carbon dioxide uptake in five-year-old mangrove stands in Jakarta. The research method used is vegetation analysis through simple random sampling. Data analysis was obtained through vegetation analysis, environmental factor analysis, and estimating carbon storage and carbon dioxide uptake in mangrove stands. The research results showed that the species growing at the research location were Rhizophora mucronata and Sonneratia caseolaris. Carbon storage in mangrove stands at the research location is 72.99 tonnes/ha, with a carbon dioxide absorption capacity of 267.63 tonnes/ha. Keywords: carbon stock, carbondioxide absorption, mangrove, guludan technique